D-Band Perfect Anomalous Reflectors for 6G Applications - Yuto Kato (IEEE, 2021)
We demonstrate anomalous reflectors at 140 GHz for the application of 6G communication coverage expansion. The reflectors are designed on cyclo-olefin polymer (COP) substrates on the basis of measured complex permittivity and conductivity at millimeter frequencies obtained with the balanced-type circular disk resonator method. From full-wave simulations, we confirm that nearly perfect anomalous reflection characteristics are realized with suppressed parasitic reflections in undesired directions. The simulated efficiencies excluding the material losses of the reflectors designed with the reflection angle $θ _{R}={30}^° $ , 45°, 60°, and 75° are 99.5%, 98.9%, 99.7%, and 99.8%, respectively. In addition, we fabricate the designed reflectors on the COP substrates and experimentally evaluate their anomalous reflection performances. The measured overall efficiencies of the reflectors with $θ _{R}={45}^° $ , 60°, and 75° are 88.0%, 83.6%, and 81.6%, respectively. This is the first demonstration of highly efficient anomalous reflectors in the D-band.